Vascular plant colonisation of four castles in southern Italy: Effects of substrate bioreceptivity, local environment factors and current management. (September 2018) - Motti, Riccardo; Bonanomi, Giuliano
Abstract: Biodeterioration, the alteration caused by living organisms, on historical buildings and stone monuments is a widespread problem affecting two-thirds of the world's cultural heritage. Deterioration and weathering of stone monuments are caused by abiotic, anthropogenic and microbial factors, with few studies focusing on the role of higher plants. In this study, we investigate how rock type, exposure and inclination of the wall, as well as current management, affect the biodeteriogenic vegetation at four stone monuments. For this purpose, we selected four castles situated in the province of Naples in southern Italy. For each castle, we analysed linear transects 1 m long (N = 74), representing the different associations of the main biodeteriogenic vascular plant species. The total number of plant species recorded was 28, belonging to 17 families. Floristic composition and hazard index (HI) varied greatly among the four study sites. Exposure, substrate type and surface inclination significantly affect floristic composition, with plant cover and HI highest on south-facing walls. As regards the rock substrate, HI was significantly higher on plaster, compared to piperno and tuffs. Finally, substrate inclination did not affect plant occurrences although the HI was significantly higher on horizontal surfaces than vertical ones. Our study revealed that the walls of four castles harboured specific flora, whose composition depends on local environmental factors, current management as well as the surrounding vegetation. The present findings concerning the colonisation capabilities of the main biodeteriogenic species provide useful insight to clarify the relationship between plant cover and hazard risk in the context of wall deterioration. Highlights: The plants growing on four castles situated in the province of Naples are studied. Vegetation composition and hazard index varied greatly among the four study sites. Exposure, substrate type and surface inclination affect vegetation composition. Plant cover was significantly higher on plaster, compared to piperno and tuffs.